Level of physical activity associated with risk of cardiovascular diseases and mortality in patients with type-2 diabetes: report from the Swedish National Diabetes Register. (29th August 2020) - Zethelius, B; Gudbjörnsdottir, S; Eliasson, B; Eeg-Olofsson, K; Cederholm, J
Abstract: Aims: To estimate risks of coronary heart disease (CHD), cardiovascular disease (CVD), and total mortality with low or higher levels of physical activity (PA) assessed with questionnaire, in an observational study of patients with type-2 diabetes from the Swedish National Diabetes Register. Subjects and methods: A total of 15, 462 patients (60 years), were followed for 5 years from baseline in 2004 until 2009, with 760 CVD events and 427 total mortality events based on 54, 344 person-years. Results: Comparing 6963 patients with low baseline PA (never or 1–2 times/week for 30 min) and 8499 patients with higher baseline PA (regular 3 times/week or more), hazard ratios for fatal/nonfatal CHD, fatal/nonfatal CVD, fatal CVD, and total mortality were 1.25 (95% CI 1.05–1.48; p  = 0.01), 1.26 (95% CI 1.09–1.45; p  = 0.002), 1.69 (95% CI 1.18–2.41; p  = 0.004), and 1.48 (95% CI 1.22–1.79; p  < 0.001), adjusting for age, sex, diabetes duration, diabetes treatment, and smoking (model 1). Adjusting also for HbA1c, systolic blood pressure, low- and high-density lipoprotein cholesterol, triglycerides, body mass index, and albuminuria (model 2), HRs were 1.19 (95% CI 1.00–1.42; p  = 0.049), 1.18 (95% CI 1.02–1.36; p  = 0.04), 1.54 (95% CI 1.07–2.22; p  = 0.02), and 1.41 (95% CI 1.16–1.72; p  < 0.001), respectively. Corresponding results (model 2), comparing 4166 patients having low PA both baseline and at follow up with all other 11, 296 patients were 1.68 (95% CI 1.41–2.01), 1.68 (95% CI 1.45–1.96), 2.12 (95% CI 1.48–3.03), and 2.03 (95% CI 1.66–2.48) (all p  < 0.001) and compared to 2797 patients with low baseline PA and higher PA at follow up were 2.51 (95% CI 1.87–3.38), 2.54 (95% CI 1.98–3.27), 3.26 (95% CI 1.74–6.10), and 2.91 (95% CI 2.08–4.07) (all p  < 0.001). Conclusions: This large observational study of patients with type-2 diabetes showed considerably increased risks for CVD and mortality with low PA.